Effect of the Turret’s Rotational Damping on the Heading Stability of a Turret-Moored FPSO - Soo Young Min; Sung Boo Park; Seong Yun Shin; Da Gyun Shin; Kwang Hyo Jung; Jaeyong Lee; Seung Jae Lee; Solyoung Han; Yun Suk Chung (한국해양공학회지, 2020)
The main features of offshore turret platforms are station-keeping and weathervaning functions. Due to the complexity of the yaw motion, abundant research is being done to verify the factors that affect the heading stability. Simulations are used for studies that are not possible with experiments, but the conditions must be verified using experimental results. This study presents methods to estimate turret-related parameters such as the rotational stiffness and rotational damping. A time series analysis was performed, and the results showed that the calculation using the obtained parameters agreed well with experimental results.